Atrazine degradation by Bacillus safensis strain BUK_BCH_BTE6 isolated from agricultural land in northwestern Nigeria - Faisal Muhammad; Hafeez Muhammad Yakasai; Mohd Yunus Shukor (Indonesian Journal of Biotechnology, 2023)
Atrazine herbicide is known to disrupt the endocrine system and is potentially carcinogenic. Its continual application leads to high residue levels in soil, causing water pollution, which when consumed is associated with devastating health effects. This research reported the isolation and characterization of a new bacterial strains from active agricultural soil with the potential to biodegrade atrazine as a sole carbon source. An enrichment method was utilized to isolate the bacteria (A1, A2, B1, B2, C1 and C2) on mineral salt media (MSM) following serial dilution. Six isolates were screened for their tolerance to various concentrations of atrazine (500 to 1500 mg∙L‐1), and only isolate B1 tolerated up to 1500 mg∙L‐1 atrazine. The isolate was identified molecularly as Bacillus safensis strain BUK_BCH_BTE6 based on 16S rRNA gene sequencing and molecular phylogenetic analysis. Characterization of the isolate based on the effects of temperature, pH, substrate concentration, incubation time, inoculum size, and heavy metals revealed optimum growth and atrazine degradation at 35 °C, a pH of 7.5, 400 mg∙L‐1, at 48 h, and inoculum size of 600 µL, respectively. The growth of the isolate was inhibited by 2 ppm Hg, Cd, Cr, Pb, Ar, and Ni, while Fe, Cu, and Zn stimulated it. GC‐MS analysis revealed a degradation efficiency of 88.85% within 120 h, while metabolites such as desethyldeisopropylatrazine, deisopropylatrazine, N‐ethylammelide, and cyanuric acid were also detected. This isolate is a highly atrazine‐tolerant and efficient atrazine degrader that could be employed for bioremediation of atrazine‐polluted sites.